KESESUAIAN PENULISAN ABSTRAK ARTIKEL JURNAL PADA SCIENCE AND TECHNOLOGY INDEX (SINTA) - Sudiar, Nining; Latiar, Hadira; Monika, Winda (Info Bibliotheca: Jurnal Perpustakaan dan Ilmu Informasi, 2024)
This study aims to evaluate the suitability of scientific article abstract writing with the standard of abstract writing in Lancang Kuning University journals indexed by Science And Technology Index (Sinta). The research methodology is quantitative, including literature search and comparative analysis of Sinta-indexed journal abstracts. The results showed that there were 22 accredited journals with different accreditation levels, ranging from Sinta 2 to Sinta 6. All journals have writing rules or guidelines, but these rules have not been followed or obeyed properly by the authors so that there are still discrepancies in abstract writing. More than half or 78.51% of the discrepancies were caused by the use of language, then 50.12% in the use of word count and 45.30% in the use of keywords. A small proportion of discrepancies, or 12.42%, were found in writing the substance of the abstract.